Derivatives of Cucurbitacin-E-glucoside produced by Curvularia lunata NRRL 2178: Anti-inflammatory, antipyretic, antitumor activities, and effect on biochemical parameters - Abdelfattah A. Abdelkhalek; Abdel-Monem M.A. Sharaf; Mohamed Rabie; Hussein I. El-Subbagh (SpringerOpen, 2017)
Cucurbitacin E glucoside (1) is a tetracyclic triterpenoid glucoside, isolated from Cucurbitaceae plants. In the present study the pharmacological and biochemical effects of cucurbitacin-E-glucoside and two of its microbial transformation derivatives (2 and 3) produced by Curvularia lunata NRRL 2178, were investigated. The isolated compounds were identified by 1H and 13C NMR spectroscopy. The obtained results showed that 2 and 3 possess anti-inflammatory and antipyretic effects, compared with indomethacin and acetaminophen. Oral administration of 2 and 3 at dose of 1/10 of LD50 for 30 days resulted in a significant decrease in the serum levels of glucose, cholesterol and triacylglycerol. Cucurbitacin-E-glucoside showed moderate cytotoxicity against tumor cell lines while compound 3 proved to be selective against colon carcinoma cell lines.